Impacts of Diatomaceous Earth on the Properties of Cement Pastes - Bashir Hasanzadeh; ZhiHui Sun (Journal of Building Materials and Structures, 2019)
Fresh properties of concrete are closely related to operation and construction, such as transporting, placing, compacting, etc.; and they also have a great impact on the lifetime performance of concrete. In this paper, the influence of Diatomaceous Earth (DE) as a natural pozzolan on fresh properties of cement pastes has been investigated. Cement pastes with different water-to-binder ratios (w/b=0.4, 0.5 and 0.6) and 0%, 2%, 6% and 10% replacement levels of DE by weight of cement were studied. Viscosity, yield stress, flow diameter, bleeding, setting times, and the heat evolution of all cement pastes were measured. Results showed that DE has a significant impact on fresh properties of cement pastes. Increasing DE content in cement pastes resulted in higher viscosity and lower flow diameters. Pastes with higher DE replacement levels showed lower bleeding rate and shorter initial and final setting times. The isothermal calorimetry test also showed that, as a pozzolanic material, DE lowered the heat of hydration, however, it advanced the appearance of the heat evolution peaks which was in agreement with the results from setting time tests.